EFFECT OF ZINC OXIDE AND ZINC BORATE ON MECHANICAL PROPERTIES OF HIGH DENSITY POLYETHYLENE - (:unkn) unknown (SERBAN SOLACOLU FOUNDATION, 2015)
The effect of zinc oxide (ZnO) and zinc borate (ZnHBO3) on the mechanical properties of high density polyethylene (HDPE) was investigated. Composites of HDPE with zinc oxide and zinc borate were prepared by melt mixing in a twin screw extruder and then the composites were molded by compression molding method. Filler contents in the HDPE were 5, 10 and 15 wt%. The dispersion of zinc oxide and zinc borate particles in the matrix polymers was investigated using SEM. It was observed that the dispersion of ZnO and ZnHBO3 particles were relatively good with low ZnO and ZnHBO3 content but the aggregates of ZnO and ZnHBO3 particles in a polymer matrix increased with increasing content. The mechanical test showed that the elasticity modulus, hardness and density of HDPE composites increased with increasing ZnO and ZnHBO3 content. The addition of fillers to the HDPE changed the wear rate of the composites as well.
Keywords: High density polyethylene; zinc oxide; zinc borate; mechanical properties; wear; ZNO NANOPARTICLES; CRYSTALLIZATION; POWDER; NANOCOMPOSITES; COMPOSITES; MORPHOLOGY